2004
DOI: 10.1902/jop.2004.75.1.146
|View full text |Cite
|
Sign up to set email alerts
|

Locally Produced Anti‐Phosphorylcholine and Anti‐Oxidized Low‐Density Lipoprotein Antibodies in Gingival Crevicular Fluid from Aggressive Periodontitis Patients

Abstract: The local production of anti-PC and anti-oxLDL further implicates the oral flora as a source of antigen that may mediate immune reactions of relevance to cardiovascular and other systemic diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
28
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 29 publications
3
28
0
Order By: Relevance
“…For this reason, increases in the plasma level of small LDLs, such as those seen in our group of GAgP subjects, may be particularly atherogenic. This notion is consistent with increased plasma titers of antioxidized LDL antibodies found in subjects with periodontitis (66)(67)(68)(69).…”
Section: Discussionsupporting
confidence: 84%
“…For this reason, increases in the plasma level of small LDLs, such as those seen in our group of GAgP subjects, may be particularly atherogenic. This notion is consistent with increased plasma titers of antioxidized LDL antibodies found in subjects with periodontitis (66)(67)(68)(69).…”
Section: Discussionsupporting
confidence: 84%
“…Elevated anti-PC antibodies have been demonstrated in periodontitis patients compared to those with no attachment loss [30] and to those with less suppuration [52]. Studies also demonstrate recognition of PC moieties on oxidized LDL by serum and gingival crevicular fluid anti-PC antibodies [50], [53]. The other oxidized epitope displaying molecular mimicry with bacterial epitopes is cardiolipin, a phospholipid located in the inner leaflet of mitochondria and present also in OxLDL and bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment effects were dependent on baseline LPS levels, with increases in HDL and LDL particle size following therapy. Using Periodontal pathogens express HSPs such as HSP-60 (GroEL) Lu & McBride 1994, Maeda et al 1994, Vayssier et al 1994, Anti-Porphyromonas gingivalis GroEL and anti-Fusobacterium nucleatum GroEL, elevated in periodontitis patients, stimulates inflammatory cytokine production as well as monocyte and endothelial cell activation Ueki et al 2002, Lee et al 2012 Elevated levels in periodontitis patients, cross-reacts with oxidized low-density lipoproteins (oxLDL) and oral bacteria Schenkein et al 1999Schenkein et al , 2001Schenkein et al , 2004 Anti-oxLDL Locally produced in gingiva, found in GCF Schenkein et al 2004, Cross-react with P. gingivalis Rgp protease Turunen et al 2012, Higher in serum of periodontitis patients, and in periodontitis patients with CVD Montebugnoli et al 2004, Monteiro et al 2009 similar methodologies, they found that HDL promoted the enhanced efflux of cholesterol from macrophages following therapy, especially in patients in which CRP levels were also reduced by periodontal treatment (Pussinen et al 2004a). Kallio (Kallio et al 2008) observed that in periodontitis patients, elevated serum LPS levels persisted following therapy and that LPS was associated with highly atherogenic lipids, including vLDL and intermediate density lipoproteins (IDL).…”
Section: Dyslipidemia Lipid Peroxidation and Inflammationmentioning
confidence: 99%